Proposta de um modelo de plano de encerramento de aterro sanitário utilizando a ferramenta de apoio multicritério à decisão - Silva, Karina Albuquerque da (2024)
Proper closure of landfills is a growing concern due to environmental and social impacts resulting from its operation. This study proposes a plan for closure of a landfill using the multi-criteria decision support tool. A research addresses the need to consider multiple criteria, such as environmental aspects, economic and social, in decision-making related to the closure of landfills. A proposed methodology includes the identification of relevant criteria, the definition of alternative closure, the application of the multi-criteria tool to evaluate the alternatives and the selection of the best closing strategy. The use of this approach aims to ensure a sustainable closure, which minimizes environmental impacts, promotes safety public and meets the needs of the local community. This study contributes to the advancement of solid waste management practices, providing a systematic model for the planning the closure of landfills. The study adopted a methodology descriptive, explanatory and exploratory, seeking to consult experts to validate the order indication of steps in a process of closing landfills. The research began with the search for bibliographies, building a theoretical basis on the subject. We used the SNOWBALL technique to select 10 experts from different areas, such as engineering environmental, biology and government agencies. The results obtained provided a comprehensive overview of experts' insights, highlighting professional diversity and institutional. Consistency in responses, especially among university professors, suggests alignment of perspectives in the academic environment. The multidisciplinary approach to professionals with training in environmental engineering and biology enrich discussions about the theme. The presence of an environmental engineer linked to an industrial construction company adds a practical perspective, connecting academia with the private sector. The agreement between professors from different universities indicates an academic consensus on certain aspects, substantiating knowledge in the area. The interconnection between theory and practice is evidenced by the participation of professionals working in the industry, highlighting the relevance from academic research to real-world challenges. The Plan model Landfill Closure proposes a strategic approach to closing these complex locations. Based on the results of a dissertation, the plan follows guidelines, emphasizing phases from diagnosis to post-closure maintenance. It stands out for consider environmental, economic and social criteria. The emphasis on rehabilitation aims to minimize impacts and integrate the area into the community. Continuous monitoring reinforces the environmental responsibility, making the plan valuable for the sustainable management of landfills.